Comparative Bioavailability and Pharmacokinetics Between the Solid Form of Metformin vs a Novel Liquid Extemporaneous Formulation in Children - Radamés Alemón-Medina; Nelly Altamirano-Bustamante; Gustavo Lugo-Goytia; Raquel García-Álvarez; Liliana Rivera-Espinosa; Luz María Torres-Espíndola; Juan Luis Chávez-Pacheco; Hugo Juárez-Olguín; Josefina Gómez-Garduño; Carmen Flores-Pérez; Paola Gabriela Fernández-Pérez (SAGE Publishing, 2021)
Metformin pharmacokinetics in a liquid extemporaneous formulation from commercial tablets was determined in paediatric patients. A randomized, transversal clinical trial was conducted in 34 children and adolescents between 7 and 17 years of age. 17 children were randomized to take metformin in the liquid formulation and, after a 1-week wash period, a 500 mg metformin tablet was administered to them. Blood samples were obtained in Whatman 903® cards at 0, 1, 2, 4, 8, 12 and 24 hours. Extraction was made by direct precipitation with acetonitrile (ACN) and methanol, detection by UPLC and tandem mass spectrometry. The method was accurate, precise, selective and linear from 50 to 1000 ng/mL (r = .9982). Comparative pharmacokinetics, tablet vs formulation, were as follows: C max 1503.2 ng/mL vs 1521.4, T max 1.5 h vs 2.3, and half-life 8.2 vs 7.5 h. The liquid formulation of metformin showed similar pharmacokinetics to the tablet, and the ratios (90% CI) of geometric mean for metformin were 100.63% (89.13-113.6), 98.08% (88.04-109.2), and 97.52% (84.9-112.01), for C max , AUC 0-t , and AUC 0-∞, respectively. Pharmacokinetics was determined using WinNonlin Pro 3.1 software. The liquid formulation of metformin showed similar pharmacokinetics to the tablet, allowing a more precise dose adjustment and ease of administration.